"How Does a Black Person Speak English?" Beyond American Language Norms. (February 2020) - Smith, Patriann
This study draws from World Englishes and a raciolinguistic perspective to examine how seven Black educators used standardized Englishes after their migration to the United States. Findings reflected sources of English (il)legitimacy to which educators were subjected based on negative reactions to their accents, race, communication, and vocabulary. In turn, cultural incongruence and confusion led educators to (re)claim their English legitimacy and to leverage pedagogical approaches regarding tone, expectation, delivery, and linguistic content and context. Through metalinguistic, metaracial, and metacultural understanding, educators reflected 'a transraciolinguistic approach, ' (re)establishing legitimacy of their standardized Englishes as Black speakers in the U.S. academy. Implications for addressing challenges to the legitimacy of certain standardized Englishes used by racialized speakers in the academy are discussed.